Liquidity Management And Financial Performance Nexus: A Micro Analysis With Glaxosmithkline Consumer Nigeria PLC - Etale, Lyndon M.; Sawyerr, Ayaundu E. (Archives of Business Research, 2020)
This study was set to investigate the link between liquidity management and financial performance of GlaxoSmithKline a leading pharmaceutical manufacturing company in Nigeria with a strong multinational background. Current ratio (CUR), quick ratio (QUR) and cash ratio (CAR) were used to represent liquidity management (the independent variables), while return on assets (ROA), proxy for financial performance was adopted as the dependent variable. Secondary data for the study was obtained from the financial statements of GlaxoSmithKline for the eight year period covering 2011 to 2018. Statistical tools employed for the analysis of data include descriptive statistics and OLS multiple regression technique applying the E-view 10 software. The results revealed that current ratio and cash ratio had significant positive effect on return on assets, while quick ratio had a significant negative link with return on assets. The study concluded that liquidity management had mixed significant economic connection with financial performance in the case of GlaxoSmithKline Consumer Nigeria PLC. The study recommended that the management of the company should pay close attention to its liquidity position by putting in place policies for efficient management of its current assets, especially inventory, accounts receivable and cash to reduce the incidence of excess liquidity in the last few years.